PELATIHAN PUBLIC SPEAKING KATEKIS VOLUNTEER SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBICARA UNTUK TAYANGAN YOUTUBE CHANNEL “SAYUKA TV” - Intan, Theresia; Maria Barbara Apul, Merlina; Revia, Brigitta (Jurnal Abdimas Musi Charitas, 2023)
This community service is a continuation of the mentoring activity "SAYUKA TV Podcast Video Production Process". In the context of the modern world, which is increasingly facilitated by the development of digital communication, Catechists as preachers of the Word of God, are not only required to have technical skills in digital media production, but the ability to speak in public with interesting and relevant content for the Catholic Church is also a necessity. This activity was also motivated by the lack of public speaking skills of Catechists when speaking in public. Public speaking can be defined as a communication process carried out by someone in front of a large audience to provide information, influence, or entertainment. The target object of this training is the Catechist Team and Social Communication (Komsos) of Santo Yusup Karangpilang Catholic Church, Diocese of Surabaya. This activity took the theme "Public Speaking Training: Talking Asik Scripture". The purpose of this activity is manifested in five main competencies that must be possessed by the trainees, namely improving communication skills, strengthening self-confidence, increasing attractiveness and influence, overcoming nervousness, and improving interaction with the audience. The training activities are divided into two stages, namely the delivery of conceptual insights (awareness and knowledge), then followed by a speaking practice session (activity). The results of this service activity show that the trainees experienced positive changes in their way of speaking, including more careful word selection and increased confidence when communicating with the audience.